Shorter Granulocyte Telomeres Among Children and Adolescents With Perinatally Acquired Human Immunodeficiency Virus Infection and Chronic Lung Disease in Zimbabwe. (8th August 2020) - Ajaykumar, Abhinav; Wong, Glenn C; Yindom, Louis-Marie; McHugh, Grace; Dauya, Ethel; Majonga, Edith; Mujuru, Hilda; Ferrand, Rashida A; Rowland-Jones, Sarah L; Côté, Hélène C F
Abstract: Background: Chronic lung disease (CLD) has been reported among African children with perinatally acquired human immunodeficiency virus (HIV) infection (C-PHIV), despite combination antiretroviral therapy (cART). In adults, shorter telomere length (TL) has been reported in association with both CLD and HIV. As little is known in children, our objective was to compare TL in HIV-positive (cART-naive or -treated) and HIV-negative children with and without CLD. Methods: Participants included Zimbabwean C-PHIV, aged 6–16, who were either newly diagnosed and cART-naive, or on cART for >6 months, and HIV-negative controls of similar age and sex. Packed blood cell (granulocyte) TLs from 621 children were compared cross-sectionally between groups. For a subset of newly diagnosed C-PHIV, changes in TL following cART initiation were evaluated. Results: C-PHIV had shorter granulocyte TL compared with uninfected peers, regardless of cART. Among 255 C-PHIV without CLD, TL was shorter in cART-naive participants. In multivariable analyses adjusted for age, sex, CLD, and HIV/cART status, shorter TL was independently associated with older age, being HIV positive, and having reduced forced vital capacity (FVC). Last, cART initiation increased TL. Conclusions: In this cohort, C-PHIV and those with reduced FVC have shorter granulocyte TL, possibly the result of increased immune activation and cellular turnover due to longstanding HIV infection with delayed cART initiation. Abstract : Children with perinatally acquired HIV infection (C-PHIV) and children presenting with reduced forced vital capacity (FVC) exhibit shorter granulocyte telomeres. Treatment-inexperienced C-PHIV, especially those with reduced FVC, have the shortest telomeres, and initiation of antiretroviral therapy improved their telomere length.